HUBUNGAN TINGKAT PENGETAHUAN IBU NIFAS DENGAN PERILAKU PERAWATAN PAYUDARA DALAM MENCEGAH BENDUNGAN ASI DI WILAYAH KERJA PUSKESMAS MASAT KABUPATEN - Gusni Rahmarianti; Elisyah Crismonica; Nora Veronica (Fakultas Pertanian, 2021)
A person's knowledge about an object contains two aspects, namely positive aspects and negative aspects. These two aspects will determine a person's attitude; the more positive aspects of the object known, the more positive the attitude towards a particular object (Wawan 2014). An initial survey conducted by researchers on postpartum women in the working area of the Masat Community Health Centre, South Bengkulu Regency, found that of the 10 postpartum women met, 5 did not know how to take care of their breasts, and of the five mothers, 3 experienced breast milk diarrhoea during the breastfeeding period. The purpose of this study was to determine the relationship between the level of knowledge of postpartum women and breast care behaviour in preventing breast milk dams in the Masat Health Centre working area, South Bengkulu Regency. This research design was of the quantitative analytic type with a cross-sectional approach. The population of this study was all postpartum women starting immediately after delivery and continuing up to 6 weeks in the Masat Health Centre working area with a sample of 40 people. Data analysis was done with the chi-square test. The results showed that most of the postpartum women had poor knowledge, namely 15 people (37.5%), and most of the postpartum women did not do breast care, namely 23 people (57.5%). The value of 2 count (8.3) > 2 table (5.591) and the value of (0.015) (0.05) There is a relationship between the knowledge of postpartum women and breast care behaviour to prevent breast milk dam in the working area of Masat Health Centre, South Bengkulu Regency.